2023
DOI: 10.1093/eurjpc/zwad125.132
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in relation with physical activity in hypertensive patients : data from a behavioral cardiology unit

Abstract: Funding Acknowledgements Type of funding sources: None. Background/Introduction Few studies have examined the relationship between exercise and adherence to antihypertensive medication, examining all possible factors contributing to blood pressure control. Purpose The purpose of our study was to access the possible dependence relationship among hypertensive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, research on true resistant arterial hypertension revealed that 25% of patients did not adhere to prescribed medications [31]. Notably, better medication adherence has been associated with improved behavioral activation [32], while another study found high medication adherence rates among 63% of respondents [33]. These findings underscore the importance of addressing medication adherence in hypertension management and highlight the need for further research into associated factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research on true resistant arterial hypertension revealed that 25% of patients did not adhere to prescribed medications [31]. Notably, better medication adherence has been associated with improved behavioral activation [32], while another study found high medication adherence rates among 63% of respondents [33]. These findings underscore the importance of addressing medication adherence in hypertension management and highlight the need for further research into associated factors.…”
Section: Discussionmentioning
confidence: 99%
“…One of these innovative strategies is represented by the promotion of healthy lifestyle behaviours, including regular physical activity. A recent study carried out in a cardiology unit involving patients suffering from hypertension has shown the positive effect of regular physical activity on adherence to medications ( Fragoulis et al, 2023 ) after a behavioral activation intervention. Thus, the authors concluded that there is the need for innovative research in this field for further confirmation of the positive relationship between treatments’ adherence and physical activity.…”
Section: Introductionmentioning
confidence: 99%